AN ANALYSIS OF LECTURER STRATEGIES IN TEACHING READING AT THE FOURTH SEMESTER OF ENGLISH EDUCATION STUDY PROGRAM IN UNIVERSITY OF MUHAMMDIYAH KOTABUMI ACADEMIC YEAR 2020/2021 - Nuraini, Puja (Griya Cendikia, 2022)
This research about reading study that analyzes the strategies used by lecturer’ in teaching reading and the reasons for using these strategies and students’ perceptions of the strategies used by lecturer’ at the Fourth Semester of English Education Study Program in University of Muhammdiyah Kotabumi. The aim of this study to find out what strategies used by lecturer in teaching extensive reading course and to find out the reasons for used strategy and the last to find out students perceptions toward the strategies used by lecturer. This research was appointed because some problems that students face in reading. The problems that students often are not understanding the meaning of what they read, difficulty when them finding new vocabulary and sometimes students lazy in reading. This research used with the research object of lecturer and students in the English extensive reading course. The location of this research at the University of Muhammadiyah Kotabumi and more specifically this research in the fourth semester of the English education study program. The method used in this research is descriptive qualitative. The instruments of this research are interview and questionnaires. The results of this study, the lecturer’ used a task based learning (TBL) strategy. TBL is a task-based strategy which contains tasks for students to be more independent in completing their assignments can improve students’ reading skills. The reason why lecturer used this strategy because this strategy can make students to always practice from the texts they read. So that in its implementation students can more easily understand the text and increase their reading ability. From the perception of students regarding the strategy used by the lecturer, the average student response to the implementation of the strategy was good Keyword: strategy, lecturer strategy, student perception